Sex Difference in Trigeminal Neuropathic Pain Response to Exercise: Role of Oxidative Stress - Zahra Rostami; Sahar Ghasemi; Hamed Farzadmanesh; Manouchehr Safari; Ali Ghanbari (Pain Research and Management)
Aim. Orofacial chronic neuropathic pain commonly occurs following trigeminal nerve injuries. We investigated whether swimming exercise can reduce trigeminal neuropathic pain through improving antioxidant capacity. Materials and Methods. Twenty-eight Wistar rats of either sex and 180–220 grams were divided into 4 groups as sham, neuropathy, neuropathy + single bout exercise, and neuropathy + 2 weeks of exercise. Trigeminal neuropathy was carried out through chronic constriction injury (CCI) of infraorbital nerve. Protocols of exercise were included a single bout session (45 minutes) and a 2-week (45 minutes/day/6 days a week) swimming exercise. Mechanical allodynia was detected using Von Frey filaments. The activity of the serum antioxidant enzymes glutathione peroxidase and superoxides dismutase was assayed using ELISA kits. Results. We found that CCI significantly reduced facial pain threshold in both sexes (P<0.05). Both swimming exercise protocols significantly reduced mechanical allodynia in female rats compared to the sham group; however, only 2 weeks of exercise were significantly effective in male rats. The activity of antioxidant enzyme glutathione peroxidase significantly (P<0.05) decreased following CCI in female rats against that in the sham group and 2-week exercise significantly (P<0.05) increased it toward the control level. The levels of glutathione peroxidase in male rats and superoxidase dismutase in both sexes were not significantly different compared to their sham groups. Conclusion. Swimming exercise alleviates trigeminal neuropathic pain in both sexes. Oxidative stress as a possible mechanism was involved in the effect of exercise on female rat trigeminal neuropathy.